Genotypic composition and performance of pea-nodulating rhizobia from soils outside the native plant-host range - Zhang, Junjie; Wang, Nan; Li, Shuo; Brunel, Brigitte; Wang, Jingqi; Feng, Yufeng; Yang, Tao; Zong, Xuxiao (Frontiers in Microbiology, 2023)
Cultivated soils need to shelter suitable rhizobia for legume cropping, especially in areas outside of the plant-host native range, where soils may lack efficient symbiotic partners. We analyzed the distribution patterns and traits of native rhizobia associated with Pisum sativum L. in soils of Hebei Province, a region that has recently experienced an expansion of pea production in China. A total of 43 rhizobial isolates were obtained from root-nodules and characterized genetically and symbiotically. The isolates discriminated into 12 genotypes as defined by PCR-RFLP of IGS DNA. Multiple locus sequence analysis (MLSA) based on the 16S rRNA, recA, atpD and gyrB of representative strains placed them into five clusters of four defined species (R. sophorae, R. indicum, R. changzhiense and R. anhuiense) and a novel Rhizobium genospecies. R. sophorae was the dominant group (58%) followed by R. indicum (23%). The other groups composed of R. changzhiense (14%), R. anhuiense (1 isolate) and the new genospecies (1 isolate), were minor and site-specific. Based on nodC phylogeny, all representatives were intermingled within the symbiovar viciae with R. sophorae and R. changzhiense being a new record. All the tested strains showed efficient symbiotic fixation on pea plants, with half of them exhibiting better plant biomass performance. This suggests that the pea-nodulating rhizobia in Hebei Province form a specific community of efficient symbiotic rhizobia on pea, distinct from those reported in other countries.